Examen Especial para verificar el cumplimiento legal desde el punto de vista Financiero al Componente Ingresos y Gastos en el GAD Guano, período 2017 - Chavarrea Pilco, Génesis Fernanda (2019)
The special examining is a fragment of audit, being it your minor reach; it is responsible for evaluating a certain part of the institution’s operations, using techniques and procedures to auditing to verify the correct management of public resources and compliance with the legal provisions in force to which it is subject. The development of the present research has as objective to determine if the special review affects the legal compliance in the Income and and Expenses accounts in the GADM - CG, in the period 2017 period. The methodology was based on a non experimental design because the variables were studied as presented without modifying them. The type of research correspond to a documentary and field process, because the information was obtained in the same place. The method applied is the deductive, because it starts from the general to the most specific, It was supported by a quantitative methodology since it was worked with numerical data. To conclude the work, four phases of the Financial Audit were carried out: Preliminary planning - general knowledge of the institution, Specific planning - evaluation of internal control, Execution - development of the special examination and determining the findings of income and expenses, Communication of the results - Writing the final report, conclusions and recommendations